Language Context and Feminism Representation in Phillis Wheatley’s Poetry: A Study of ‘On Being Brought From Africa to America’ - Setiadi, Christopher (LITERA : Jurnal Bahasa Dan Sastra, 2025)
Poetry is not only a form of creative writing. This literary works also can be used as an act to share an idea and come as an act of formation into the society. In this case, Phillis Wheatley as an African-American woman wrote “On Being Brought from Africa to America” come as an agent of change of inequality in a part of racial issue. The poetry itself talking about her thoughts about religious aspect and also in her society which is segregation between White People and Black People. The research came up to analyze its language context from its poetry and find out a feminism representation through a literary works perspective. In this study, the researcher uses a qualitative descriptive approach to analyze the poetry. Furthermore, there are some aspects that can be concluded in this research after it is conducted. First in language context, it is found that the poetry “On Being Brought from Africa to America” affected based on external influence and religious imagery. Second in feminism aspect, this poetry represent women which Phillis Wheatley pass the three phases of tradition writing in a form by woman which lead creativity became an act of expression in social issue.